Antar Pakatan and the Reproduction of Social Solidarity: A Cultural Strategy for Addressing the Economic Burden of Customary Marriage in the Sambas Malay Community - Muhammad Syarif; Khamim (Indonesian Journal of Sharia and Socio-Legal Studies, 2025)
In communal societies, the celebration of traditional weddings often places a significant financial burden on host families, particularly in communities that uphold strong cultural values and social honor. This challenge is also faced by many lower- to middle-income families in Sambas Regency, West Kalimantan. This article analyzes the antar pakatan tradition practiced by the Sambas Malay community as a culturally embedded social strategy to mitigate the high costs associated with customary wedding ceremonies. Utilizing a qualitative field research methodology with a socio-legal approach, the study draws on in-depth interviews and non-participant observations conducted in Sepadu Village, Sambas Regency. The findings reveal that antar pakatan functions as an informal mechanism of economic redistribution, grounded in the values of mutual assistance and collective participation, which are realized through voluntary contributions from guests. This tradition effectively alleviates financial pressure without diminishing the symbolic significance of customary rituals, while reinforcing social solidarity through culturally institutionalized reciprocal relationships. This article argues that antar pakatan represents a customary institution capable of bridging the sustainability of tradition with the need to adapt to contemporary economic challenges. Furthermore, it contributes theoretically to the study of social exchange dynamics within value-based communal societies. [Dalam konteks masyarakat komunal, pelaksanaan pesta pernikahan adat sering kali menjadi beban ekonomi yang signifikan bagi keluarga penyelenggara, terutama dalam komunitas yang menjunjung tinggi nilai-nilai kultural dan kehormatan sosial. Hal serupa juga dialami oleh sebagian keluarga yang berpenghasilan menengah ke bawah di Kabupaten Sambas. Artikel ini bertujuan untuk menganalisis tradisi antar pakatan yang dipraktikkan oleh komunitas Melayu sebagai solusi sosial berbasis kearifan lokal dalam menghadapi tingginya biaya penyelenggaraan pernikahan adat. Penelitian ini menggunakan metode kualitatif lapangan dengan pendekatan sosio-legal, melalui wawancara mendalam dan observasi non-partisipan yang dilaksanakan di Desa Sepadu, Kabupaten Sambas. Hasil penelitian menunjukkan bahwa tradisi antar pakatan berfungsi sebagai mekanisme informal redistribusi ekonomi yang dilandasi nilai gotong-royong dan partisipasi kolektif, yang diwujudkan melalui kontribusi sukarela dari tamu undangan. Tradisi ini secara efektif mereduksi tekanan finansial tanpa menghilangkan makna simbolik dalam penyelenggaraan adat, sekaligus memperkuat solidaritas sosial melalui relasi timbal balik yang dilembagakan secara kultural. Artikel ini berargumen bahwa tradisi antar pakatan merepresentasikan pranata adat yang mampu menjembatani antara keberlanjutan tradisi dan adaptasi terhadap tantangan ekonomi kontemporer, serta memberikan kontribusi teoretis terhadap kajian mengenai dinamika pertukaran sosial dalam masyarakat berbasis nilai.]